Faktor-faktor yang mempengaruhi minat belanja online masyarakat (studi kasus pengikut instagram muslimah thread) - Nurjanah, Rahma; Vyn Amzar, Yohanes; Rizkiah, Nadia (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The purpose of this study was to partially determine respondents' characteristics and the effect of promotion, product price, and shopping experience on people's online shopping interest. This study was conducted using a Likert scale shared with google form via Instagram @Muslimahthread_, from the results of the data obtained from the Likert scale then processed with multiple regression models. From the results of the study, it was found that the characteristics of the respondents were dominated by respondents aged between 14 – 23 years (84.6%), educated in junior high and high school equivalents (82.4%), unmarried (90%), status as students (62%), came from Java Island (67.4%), those who were already working had incomes between IDR 300,000 – IDR 2,522,278 (49%) and those who had not worked had revenues between IDR 60,000 – IDR 1,239,621 (92,4%). With expenses between IDR 35,000 – IDR 941,341 per month (79.6%), the average nominal online shopping transaction is between IDR 20,000 - IDR 359,095 per month (84.2%), having no side job (76.9%), the most popular types of products are Fashion and Beauty Products (78.3%), and the most frequently used type of payment COD or Cash on Delivery (40.7%). The results of multiple linear regression indicate that Promotion and Shopping Experience has a significant effect on Online Shopping Interest. Meanwhile, product prices have no significant impact on online shopping interest.